ForumSpace - Meducator, The; Gao, Chloe; Sharma, Kartik; Belesiotis, Peter (The Meducator, 2019)
ForumSpace is a collaborative initiative between The Meducator and the McMaster Student Health Forum subcommittee. It aims to discuss important topics concerning the multi-dimensional aspects of healthcare, and the role of various stakeholders in ensuring its effective delivery.